The International Commonality of Idiosyncratic Variances - Bekaert, Geert; Wang, Xue; Zhang, Xiaoyan (Management Science, 2025)
We document strong global commonality in country idiosyncratic return variances across 23 developed markets, which is stronger than international return commonality. The global common factor of idiosyncratic return variances is highly correlated with that of idiosyncratic cash flow variances and is also significantly related to variables capturing aggregate discount rate variation and the conditional market variance. Furthermore, aggregate idiosyncratic return and cash flow variances are mostly but not always countercyclical. This paper was accepted by Kay Giesecke, finance. Funding: X. Zhang acknowledges financial support from the National Natural Science Foundation of China [Grant 72350710220] and the Beijing Natural Science Foundation [Grant IS23127]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01398 .